Assessment of Genetic Variability, Heritability and Genetic Gain for Yield and Quality Traits in Onion (Allium cepa L.) - Bal, Solanki; Maity, Tapan Kumar; Maji, Anirban (International Journal of Bio-resource and Stress Management, 2022)
The experiments were undertaken at ‘C’ Block Farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, Nadia, West Bengal, India during 2017–18 and 2018–19 to study the genetic variability, heritability and genetic gain of 23 onion genotypes. Twenty open-pollinated varieties, two hybrid varieties were taken under consideration with one variety taken as standard check. Characters like number of leaves at 30 DAT and 90 DAT, neck thickness, number of scales per bulb, bolters, average weight of 10 bulbs, vitamin C content, dry matter, TSS, phenol content, severity of purple blotch disease, total yield and marketable yield expressed high heritability along with high genetic gain. These traits were least influenced by environmental effect, so, additive genetic effect might be the influential factor for expression of such traits. Traits with such high heritability values gives clear indication that the variability observed was mainly under genetic control and offers ample scope and opportunities to conduct selection based on phenotypic performances for improvement in future onion breeding programme. For traits with moderate heritability viz., double bolters, pyruvic acid, total sugar, storage loss, selection would be less effective in these traits but can still be taken up. Characters plant height at 90 DAT and unmarketable yield, which expressed low heritability are governed by non-additive genes and therefore, hybridization between diverse parents will be the best strategy for their improvement.